(untitled) (Global Journal of Management and Business Research, 2022)
This paper examined the effect of quality control on organizational product and the needs for sustainability Innoson Motors in Anambra State, Nigeria. The paper formulated two research questions and two hypotheses which were tested at 0.05 level of significance using Spearman#x2019;s Rank Order Correlation Coefficient. Cross-sectional survey was used in collecting data for the study. The paper revealed that there is strong link between quality control and sales, and there is a perfect linear relationship between sales volume and product quality. The paper recommends that management should organize seminars, workshops on quality control for their staff to enhance sales and sustainability.